2014
DOI: 10.3390/toxins6102872
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytotoxicity, Genotoxicity and Hematotoxicity of the Recombinant Spore-Crystal Complexes Cry1Ia, Cry10Aa and Cry1Ba6 from Bacillus thuringiensis in Swiss Mice

Abstract: The insecticidal properties of Cry-endotoxins from Bacillus thuringiensis (Bt) have long been used as spore-crystals in commercial spray formulations for insect control. Recently, some Bt-endotoxin genes have been cloned in many different plants. Toxicological evaluations of three spore-crystal endotoxins, BtCry1Ia, BtCry10Aa and BtCry1Ba6 from B. thuringiensis, were carried out on mice to understand their adverse effects on hematological systems and on genetic material. These three spore-crystals have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…So, because there have been no reports of known receptors in the gut cells of the vertebrates and the physiology of their digestive system, δ-endotoxins have been considered as presenting inconsiderable toxicity to humans and other mammals [ 25 , 26 ]. However, the literature addressing the biosafety of δ-endotoxins for non-target organisms is scarce, and our present and previous works [ 19 , 21 ] have demonstrated hematotoxicity mainly for the erythroid lineage of mice after a single oral administration, corroborating another study demonstrating in vitro hemolysis in cell lines of rat, mouse, sheep, horse, and human erythrocytes [ 27 ]. This data suggests that the plasma membrane of erythrocytes could be the primary target for these toxins [ 19 , 27 ], and that Cry toxins are not completely destroyed in the stomach, having their toxic form activated by intestinal alkaline pH.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…So, because there have been no reports of known receptors in the gut cells of the vertebrates and the physiology of their digestive system, δ-endotoxins have been considered as presenting inconsiderable toxicity to humans and other mammals [ 25 , 26 ]. However, the literature addressing the biosafety of δ-endotoxins for non-target organisms is scarce, and our present and previous works [ 19 , 21 ] have demonstrated hematotoxicity mainly for the erythroid lineage of mice after a single oral administration, corroborating another study demonstrating in vitro hemolysis in cell lines of rat, mouse, sheep, horse, and human erythrocytes [ 27 ]. This data suggests that the plasma membrane of erythrocytes could be the primary target for these toxins [ 19 , 27 ], and that Cry toxins are not completely destroyed in the stomach, having their toxic form activated by intestinal alkaline pH.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, the applicability of Cry1Ac proteins as potential tools in combating diseases in humans and other mammals further highlights the importance of studies directed to the biosafety of non-target organisms. This is mainly because although Cry toxins have been considered harmless to humans and other vertebrates [ 2 , 18 ], studies by our group have demonstrated that Bt spore-crystals caused hematologic disturbances for the erythroid and lymphoid lineages of Swiss mice [ 19 , 20 , 21 ], indicating that each spore-crystal endotoxin presents a characteristic profile of toxicity and might be investigated individually [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As far as potential effects on health are concerned, several authors [38–43] show that Cry proteins could potentially have an impact on the health of mammals. Also de Souza Freire et al [44] confirm haematoxicity of several Cry toxins. Some of these effects seem to occur where there are high concentrations and tend to become stronger after several days.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of aspartate aminotransferase (AST), alanine aminotransferase (ALT), serum creatinine (Scr), and blood urea nitrogen (BUN) were calculated with the use of a Biochemical Auto-analyzer (7170S, Hitachi, Japan). [ 30 , 31 ]…”
Section: Methodsmentioning
confidence: 99%